2021
DOI: 10.17762/jaz.v42i01.6
|View full text |Cite
|
Sign up to set email alerts
|

Biochar in Cattle Farming: An Innovative Solution for Soil Fertility and Cattle Productivity

Abstract: Biochar as a soil amendment is increasingly popular in agricultural sector in the past few years. The production and application of biochar is increasing in a constant rate to meet farm requirements. Biochar is similar to charcoal and activated charcoal, which are pyrogenic carbonaceous matter derived from organic carbon rich matter through pyrolysis. The primary products generated by pyrolysis are biochar, syngas and bio-oils depending on biomass and pyrolysis conditions. The quality of biochar is according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Variations in the severity of infections with the prevalence of mild positivity seen in this study might be associated with the number of infected organs, parasitic overload, age and strength of the immune response, Sarcocystis species, and single or mixed infection (Burezq, 2021;Singh, 2020). Fayer (2004) reported that the severity of infection is dependent on a dose of ingested sporocysts.…”
Section: Discussionmentioning
confidence: 56%
“…Variations in the severity of infections with the prevalence of mild positivity seen in this study might be associated with the number of infected organs, parasitic overload, age and strength of the immune response, Sarcocystis species, and single or mixed infection (Burezq, 2021;Singh, 2020). Fayer (2004) reported that the severity of infection is dependent on a dose of ingested sporocysts.…”
Section: Discussionmentioning
confidence: 56%
“…This antigen has been shown to react with some, but not all, blood samples from humans, dogs, sheep, and rams infected with Brucella spp. In addition, has been clearly shown to react with positive pooled human serum 10 . In Addition, it has been reported that immunization of animals with rOmp31 encoded for B. ovis, alone or in combination with B. ovis -type R-LPS, resulted in the development of tolerable defenses against B. ovis infection in the immunized mice 25 .…”
Section: Source: Authorsmentioning
confidence: 98%